2009
DOI: 10.1002/ijc.24686
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of cystatin M promoter is associated with unfavorable prognosis in operable breast cancer

Abstract: The methylation status of cystatin M (CST6) gene in breast tumors was investigated and its prognostic significance as a novel breast cancer biomarker was evaluated. Using methylation-specific PCR (MSP), CST6 promoter methylation was examined in 134 formalin fixed paraffin-embedded tissues (FFPEs): 10 pairs of breast tumors and their surrounding normal tissues, 10 breast fibroadenomas, 11 normal breast tissues and 93 breast tumors. Methylation of CST6 promoter was observed in 2/21 (9.5%) noncancerous breast tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 26 publications
3
28
0
2
Order By: Relevance
“…A recent functional epigenetic study identified CST6 as 1 of 8 genes that showed frequent (Ͼ30%) tumor-specific promoter region hypermethylation associated with transcriptional silencing and that its re- expression suppressed the growth of renal cell carcinoma cell lines (36 ). Moreover, according to our recent findings, CST6 methylation is a promising biomarker for prediction of relapses and deaths in operable breast cancer (24 ). Here we provide evidence that the CST6 promoter is methylated in CTCs.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…A recent functional epigenetic study identified CST6 as 1 of 8 genes that showed frequent (Ͼ30%) tumor-specific promoter region hypermethylation associated with transcriptional silencing and that its re- expression suppressed the growth of renal cell carcinoma cell lines (36 ). Moreover, according to our recent findings, CST6 methylation is a promising biomarker for prediction of relapses and deaths in operable breast cancer (24 ). Here we provide evidence that the CST6 promoter is methylated in CTCs.…”
Section: Discussionsupporting
confidence: 74%
“…MSP products were fractionated on 2% agarose gels containing 40 mmol/L Tris-acetate/1.0 mmol/L EDTA (pH 8.0). To avoid false-negative results, we amplified SBtreated DNA in 2 separate MSP reactions, 1 with a set of primers specific for methylated and 1 for unmethylated CST6 promoter sequences (24 ). We used human placental genomic DNA (gDNA; Sigma-Aldrich) methylated in vitro with SssI methylase (NEB), after SB conversion, as a fully methylated (100%) MSP positive control; we used the same unmethylated placental gDNA, after SB conversion, as a negative MSP control.…”
Section: Methylation-specific Pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…The breast cancer cell line MCF-7 was used as a positive control in MSP reactions for the detection of SOX17 promoter methylation. Genomic DNA (gDNA) from both FFPEs and MCF-7 cells was isolated with the High Pure PCR template preparation kit (Roche) as previously described (19 ). DNA concentration was determined in the Nanodrop ND-1000 spectrophotometer (Nanodrop Technologies).…”
Section: Dna Isolation From Primary Breast Cancer Ffpementioning
confidence: 99%